2020
DOI: 10.3126/jgmcn.v13i2.31947
|View full text |Cite
|
Sign up to set email alerts
|

Indications for removal of impacted mandibular third molars and associated pathologies

Abstract: Introduction: The purpose of this study was to assess the various indications of impacted mandibular third molar removal and pathologies associated with it. Methods: A retrospective cross-sectional study was conducted in the Department of Oral Surgery, Gandaki Medical College. The clinical case records from September 2016 to August 2019 were retrieved, reviewed, and analyzed. Surgically removed impacted mandibular third molars for which orthopantomogram were available and the lesions verified histologica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
(34 reference statements)
0
1
0
Order By: Relevance
“…This leads to timely diagnosis and subsequent treatment, extraction of MTM. 7%) this may be due to the fact that only impacted teeth were studied in that study; both erupted and impacted MTM were studied in our study 10. Study in Sweden by Lysell et al have shown prophylactic removal (n=229; 30%) as the common reason for extraction of MTM 9.…”
mentioning
confidence: 69%
See 1 more Smart Citation
“…This leads to timely diagnosis and subsequent treatment, extraction of MTM. 7%) this may be due to the fact that only impacted teeth were studied in that study; both erupted and impacted MTM were studied in our study 10. Study in Sweden by Lysell et al have shown prophylactic removal (n=229; 30%) as the common reason for extraction of MTM 9.…”
mentioning
confidence: 69%
“…9 According to the study done in Nepal, recurrent pericoronitis (62.9%) followed by caries (11.7%) was the most common indication for removal of impacted MTM. 10 However, there is lack of literature regarding the causes of MTM extraction when both erupted and impacted MTM are taken in account. This study was aimed to assess the reasons for MTM extraction.…”
Section: Introductionmentioning
confidence: 99%
“…Current study was comparable to the studies conducted in past. [17,18] In countries where dental checkups begin at an earlier age, impactions are more likely to be identified. [19] However, in resource-poor nations like Tanzania, most patients seek medical attention only when they are experiencing symptoms that cause them to become temporarily unable to do their daily activities, such as mild to severe pain, swellings, trismus, or fever.…”
Section: Discussionmentioning
confidence: 99%